Computer oriented numerical methods: theory, problems, algorithms and implementation using c , c++ and fortran languages - Salaria, R.S
Computer oriented numerical methods: theory, problems, algorithms and implementation using c , c++ and fortran languages / Salaria, R.S. -- New Delhi: Khanna Book Publoshing Co. 515 Sa159e5 5th ed